Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s13300-018-0519-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Different Stages of Diabetic Nephropathy and Neuropathy in Patients with T2DM: A Cross-Sectional Controlled Study

Abstract: IntroductionEarly detection of diabetic peripheral neuropathy (DPN) is critical in patients with type 2 diabetes mellitus (T2DM) due to the lack of targeted therapy for DPN. We have investigated the relationship between different stages of diabetic nephropathy and DPN in an attempt to elucidate whether albuminuria can be used as an early warning signal of DPN progression.MethodsA total of 217 T2DM patients who met the inclusion criteria were recruited from the Department of Endocrinology, Nanfang Hospital betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Urinary albumin excretion rate can be used as predicting DPN process. [42][43][44] Changes in urine albumin-to-creatinine ratio (≥30%) increase the risk for new-onset DPN in type 2 diabetes (OR = 3.059, 95% CI 1.012-9.249). 45 Furthermore, diabetic retinopathy, especially severe diabetic retinopathy is correlated with DPN; and DPN was a factor like a tell-tale sign of diabetic retinopathy; thus, it is necessary to examine more intensive ophthalmic disease.…”
Section: The Prevalence Of Peripheral Diabetic Neuropathy and Risk Factorsmentioning
confidence: 99%
“…Urinary albumin excretion rate can be used as predicting DPN process. [42][43][44] Changes in urine albumin-to-creatinine ratio (≥30%) increase the risk for new-onset DPN in type 2 diabetes (OR = 3.059, 95% CI 1.012-9.249). 45 Furthermore, diabetic retinopathy, especially severe diabetic retinopathy is correlated with DPN; and DPN was a factor like a tell-tale sign of diabetic retinopathy; thus, it is necessary to examine more intensive ophthalmic disease.…”
Section: The Prevalence Of Peripheral Diabetic Neuropathy and Risk Factorsmentioning
confidence: 99%
“…Our study provided further evidence that supported the potential role of diabetic vasculopathy in the development of DPN, since we found that patients with DPN had higher CysC, Cr, urinary ACR, and lower DBP, eGFR, ABI than those without DPN. Diabetic nephropathy (DN), a complication characterized by a decreased eGFR, increased urinary ACR, and high levels of Cr [30], is one of the most feared diabetic chronic microvascular complications, and is independently associated with DPN [31]. The urinary ACR, a marker of DN, is used as a proxy for damage to the systemic microcirculation and predicts future progression of renal dysfunction and various cardiovascular events in several populations [32].…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological assessments for DPN in the hospital of this research have been published in previous studies [11]. In brief, the Nicolet VikingQuest electromyograph system (VIASYS Healthcare, Conshohocken, PA, USA) was used for electrophysiological assessments by the same electrophysiologist.…”
Section: Clinical Data and Laboratory Assessmentmentioning
confidence: 99%
“…Taking the negative impact on the family life and social activities into account, early diagnosis and treatment of DMED is essential and may prevent or delay disease progression. Although previous studies have analyzed the risk factors between ED and T2DM, there is no definite prophylactic treatment timing window to make the clinical decision to treat DMED, especially before the onset of clinical symptoms [3,[11][12][13][14][15][16][17][18]. In order to improve the management of DMED, this study was designed not only to offer further data on the risk factors but also to identify a superior cutoff point for early DMED detection and treatment.…”
Section: Introductionmentioning
confidence: 99%